Standard implementation trajectories for sustainable product design: A configurational approach - Armand Smits; Viktoria Drabe; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2016)
While sustainability issues increasingly gain importance for new product design, they also further complicate the NPD process. In many cases it is hard to exactly measure the socio-environmental impact of new products, and sustainability targets may conflict with other ones. Innovators can aim to manage these challenges by turning to voluntary sustainability standards (VSS), like the practices and certificates that come with the EU Ecolabel, Greenguard or Cradle to Cradle standards. VSS are predefined rules, procedures, and methods for common and voluntary use and focus on social and environmental performance. It is proposed that the local implementation of these general standards from outside the organization will likely lead to a variety of firm-specific implementation trajectories, ultimately leading to different levels of VSS implementation extensiveness across firms. This variety that is not sufficiently addressed in extant research, is researched in the current study. Using organizational learning as theoretical lens this study investigates configuration(s) of factors, including the embeddedness of the relationship between the focal firm and standard specific organizations that drive VSS implementation extensiveness. In doing so, it uses the configurational research approach fuzzy set Qualitative Comparative Analysis (fsQCA). Empirically the study draws on qualitative and quantitative data from an international collection of firms that implemented the Cradle to Cradle standard. The study shows that VSS are multifaceted and that configurations that consistently drive VSS certification extensiveness differ from the ones that drive VSS practice implementation extensiveness. Additionally, it is found that configurations that consistently lead to the absence of high implementation extensiveness do not simply mirror the ones for high implementation extensiveness but have unique properties. Finally the study illustrates that similar levels of implementation extensiveness can result from multiple distinct configurations. The study mainly contributes to extant research on sustainable product design and how to integrate general principles of sustainable design into the NPD process.
Keywords: 330; sustainable product design; voluntary sustainability standards; fsQCA; implementation; Cradle to Cradle